2020
DOI: 10.1016/j.ijer.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and research: Specificity and congruence of university faculty achievement goals

Abstract: Teaching and research are core tasks of university faculty. Previous research has documented the power of achievement goal theory for describing university scholars' motivations. For theory, research, and practical implications it is crucial to have knowledge about the separability, associations , differences, and interplay of scholars' goals for teaching and research. Hence, we report two studies with 1151 and 771 German university scholars. We found that their goals can be separated between both domains whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 70 publications
(112 reference statements)
4
20
0
Order By: Relevance
“…As mentioned by Hagenauer and Volet (2014b) , teachers who primarily self-identify with their researcher role may hold different perceptions and values compared to those who identify more as a lecturer or supervisor. Indeed, empirical research documented that role conflicts between teaching and research and academics’ attitudes regarding the interrelatedness of these domains is tied to aspects of their well-being ( Daumiller and Dresel, 2018 , 2020 ). Extending this logic implies that not only switching between teaching and research roles, but also switching between different teacher roles (lecturer and supervisor) might be conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned by Hagenauer and Volet (2014b) , teachers who primarily self-identify with their researcher role may hold different perceptions and values compared to those who identify more as a lecturer or supervisor. Indeed, empirical research documented that role conflicts between teaching and research and academics’ attitudes regarding the interrelatedness of these domains is tied to aspects of their well-being ( Daumiller and Dresel, 2018 , 2020 ). Extending this logic implies that not only switching between teaching and research roles, but also switching between different teacher roles (lecturer and supervisor) might be conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Both students and teachers mentioned numerous responsibilities and demands that created stress, but also that different aspects that may be considered as personal resources, such as resilience growth or maintaining work-life balance, seemed to help. Second, numerous passages in our interview data reflected the usefulness of Achievement Goal Theory as a lens for investigating well-being, which characterizes motivation as “more or less strong strivings toward task mastery and competence development or toward superiority and competence demonstration” ( Daumiller and Dresel, 2020 , p.1). Specifically, in describing their well-being experiences, students and teachers seemed to reflect different goal orientations, such as learning goals (being focused on gaining knowledge and competencies), relational goals (being focused on fostering close and caring relationships), appearance avoidance goals (being concerned with appearing incompetent to others), and work avoidance goals (being focused on getting by with little effort).…”
Section: Discussionmentioning
confidence: 99%
“…The structure and usefulness of the above-mentioned achievement goals, as well as their relevance for explaining individual differences in achievement-related experiences and behaviors, has been confirmed in the population of higher education teachers (e.g., Daumiller, Bieg et al, 2020;Daumiller et al, 2019;Daumiller & Dresel 2020a;Daumiller & Dresel, 2020b;Hein et al, 2019;Janke et al, 2019;Rinas et al, 2020). This line of faculty motivation research has largely relied on the overview model developed by Daumiller et al (2019), which has been found to be suitable for characterizing higher education teachers' achievement goals.…”
Section: An Achievement Goal Approach To Higher Education Teachers' Mmentioning
confidence: 96%
“…Within this, established goal classes from prior frameworks and research were integrated into a comprehensive model suitable for characterizing the full scope of university instructors’ achievement goals (see Daumiller et al, 2019b , for details). Based on this model and the respective scale, a series of studies have been conducted and have proven their suitability for assessing university instructors’ achievement goals as well as their relevance for explaining differences in their experiences and behaviors (e.g., Daumiller et al, 2019a , 2020b ; Hein et al, 2019 ; Janke et al, 2019b ; Daumiller and Dresel, 2020a , b ). We therefore also adopted this achievement goal model in the present study given prior empirical evidence and its theoretical fittingness.…”
Section: Introductionmentioning
confidence: 99%